Towards Mindless Stress Regulation in Advanced Driver Assistance Systems: A Systematic Review - Béquet, Adolphe J.; Hidalgo-Muñoz, Antonio R.; Jallais, Christophe (Frontiers in Psychology, 2020)
Stress can frequently occur in the context of driving. Its cognitive effects can be deleterious for the driving task and can lead to uncomfortable or risky situations. Stress detection in driving context is well developed, while stress regulation using dedicated ADAS, despite being desirable to ensure the safety of drivers, is still emergent. This systematic review focuses on stress regulation strategies that can be qualified as “subtle” or “mindless”: this imply that the technique used to perform the regulation does not interfere with an ongoing task. This study aimed to 1) draw the state of the art on such techniques in driving context and 2) identify complementary techniques relying on subtle presentation that could be applied in driving. Systematic review was conducted using search operators previously identified through a concept analysis. The review was performed on patents and on scientific studies in order to have an overview of what kind of technological applications are proposed and to compare and discuss them under a scientific perspective. A classification of results was performed to separate types of regulation strategies used, in order to better understand underlying mechanisms for each technique found. A total of 47 publications were retrieved, including 21 patents and 26 studies. 6 of the studies investigated mindless stress regulation in driving context. The review allowed to identify several ADAS using mindless computing technologies to reduce stress, and to better understand the underlying mechanisms allowing stress reduction. Furthermore, despite further studies would be necessary to better grasp the effect of mindless technologies on the driving safety, it has been possible to establish the feasibility of their implementation as ADAS and to draw directions for future research in this field.